Designer's approach for scene selection in tests of preference and restoration along a continuum of natural to manmade environments - Hunter, MaryCarol R.; Askarinejad, Ali (Frontiers in Psychology, 2015)
It is well-established that the experience of nature produces an array of positive benefits to mental wellbeing. Much less is known about the specific attributes of green space which produce these effects. In the absence of translational research that links theory with application, it is challenging to design urban green space for its greatest restorative potential. This translational research provides a method for identifying which specific physical attributes of an environmental setting are most likely to influence preference and restoration responses. Attribute identification was based on a triangulation process invoking environmental psychology and aesthetics theories, principles of design founded in mathematics and aesthetics, and empirical research on the role of specific physical attributes of the environment in preference or restoration responses. From this integration emerged a list of physical attributes defining aspects of spatial structure and environmental content found to be most relevant to the perceptions involved with preference and restoration. The physical attribute list offers a starting point for deciphering which scene stimuli dominate or collaborate in preference and restoration responses. To support this, functional definitions and metrics - efficient methods for attribute quantification are presented. Use of these research products can provide a) greater control in the selection and interpretation of the scenes/images used in tests of preference and restoration and b) an expanded evidence base for wellbeing designers of the built environment.